Progressive sarcoma Kaposi after COVID-19 - Molochkova, Julia; Kartashova, Maria; Monaenkova, Maria (Journal of Pakistan Association of Dermatologists, 2023)
This article deals with the sarcoma kaposi worsening after severe coronavirus infection. After 2 years of sarcoma Kaposi remission a 70-year-old male HIV-negative patient noted new violaceous skin nodules. A few months before he recovered from COVID-19. We present the case and review of literature.